Situation Report: Bulgaria, 28 April 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgarian-Czechoslovak Relations Exchange of Notes between Bulgaria and Yugoslavia Continues First Quarters Plan Fulfillment Spring Situation in Agriculture Miscellaneous Bulgarian UN Representative Continues Middle East Tour Bulgarian Delegation in Tunis Belgian Communist Party Delegation in Sofia Symposium on Ethnography of the Balkan Nations Bulgarian-Czechoslovak Cooperation Yugoslavia Imports Bulgarian-Made Renault Cars Turkish Delegation in Sofia Bulgarian Deputy Minister Visits FAO in Rome Soviet Komsomol Delegation in Sofia